Advances on Cellular Clonotypic Immunity in Amyotrophic Lateral Sclerosis - Giuseppe Schirò; Vincenzo Di Stefano; Salvatore Iacono; Antonino Lupica; Filippo Brighina; Roberto Monastero; Carmela Rita Balistreri (Brain Sciences, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal neuromuscular disease, characterized by the progressive degeneration of the upper and lower motor neurons in the cortex and spinal cord. Although the pathogenesis of ALS remains unclear, evidence concerning the role of the clonotypic immune system is growing. Adaptive immunity cells often appear changed in number, or in terms of their activation profiles, both peripherally and centrally; however, their role in ALS appears conflictive. Data from human and animal model studies, which are currently reported in the literature, show that each subset of lymphocytes and their mediators may mediate a protective or toxic mechanism in ALS, affecting both its progression and risk of death. In the present review, an attempt is made to shed light on the actual role of cellular clonotypic immunity in ALS by integrating recent clinical studies and experimental observations.